Urine-Derived Stem Cells Versus Their Lysate in Ameliorating Erectile Dysfunction in a Rat Model of Type 2 Diabetes - Galhom, Rania A.; Korayem, Horeya Erfan; Ibrahim, Mahrous A.; Abd-Eltawab Tammam, Ahmed; Khalifa, Mohamed Mansour; Rashwan, Eman K.; Al Badawi, Manal H. (Frontiers in Physiology, 2022)
Background: Diabetic erectile dysfunction (DED) is a significant consequence of diabetes mellitus, and it is a multifactorial phenomenon that has no definitive treatment till now. Many therapeutic options provide symptomatic improvement rather than addressing the underlying etiology or restoring normal function. Stem cells (SCs) therapy represents a potential hope in DED management. It is well established that the regenerative effect of stem cells can be attained by their paracrine action and their ability to differentiate into many cell lineages, including endothelial and smooth muscle cells. Hence, we tried to compare the effects of transplantation of urine-derived stem cells (USCs) or their lysate (USCs-L) into the corpora cavernosa (CC) of rats with DED. Materials and Methods: Fifty-five adult male Wistar rats were included in this study. USCs were obtained from ten healthy rats. Another ten rats did not subject to any intervention and served as control (group I). Type 2 DM and DED were induced in the remaining thirty-five rats, but DED was tested and proved in only twenty-four rats, which were randomly divided into three groups (n=8 in each). DED group (group II) and either USCs (2X106 cells) or their lysate (200µL) were transplanted into the CC of each rat in the other two groups (group III and IV), respectively. Results: Although the DED rats exhibited deterioration in all copulatory functions as compared to the control group, our histopathological, immunohistochemical, and morphometric results revealed that both USCs and USCs-L have significantly restored the cavernous spaces, the ultrastructures of the endothelium that line the cavernous spaces, collagen/smooth muscle ratio and the mean area percentage of α-SMA in the CC as compared to DED rats. A respectable number of USCs was detected in the CC of group III at the 4th week after transplantation, but this number was significantly declined by the 8th week. Conclusion: Both USCs and USCs-L can repair the structure and ultrastructure of CC and improve the copulatory functions in the DED rat model. However, USCs-L could be better used in DED to guard against the strange behavior of USCs after transplantation and their decreased survivability with time.